Changes in body composition and metabolic profile during interleukin 6 inhibition in rheumatoid arthritis. Issue 4 (18th March 2017) - Tournadre, Anne; Pereira, Bruno; Dutheil, Fréderic; Giraud, Charlotte; Courteix, Daniel; Sapin, Vincent; Frayssac, Thomas; Mathieu, Sylvain; Malochet‐Guinamand, Sandrine; Soubrier, Martin
Abstract: Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by increased mortality associated with cardiometabolic disorders including dyslipidaemia, insulin resistance, and cachectic obesity. Tumour necrosis factor inhibitors and interleukin 6 receptor blocker licensed for the treatment of RA decrease inflammation and could thus improve cardiovascular risk, but their effects on body composition and metabolic profile need to be clarified. We investigated the effects of tocilizumab (TCZ), a humanized anti‐interleukin 6 receptor antibody, on body composition and metabolic profile in patients treated for RA. Methods: Twenty‐one active RA patients treated with TCZ were included in a 1 year open follow‐up study. Waist circumference, body mass index, blood pressure, lipid profile, fasting glucose, insulin, serum levels of adipokines and pancreatic/gastrointestinal hormones, and body composition (dual‐energy X‐ray absorptiometry) were measured at baseline and 6 and 12 months of treatment. At baseline, RA patients were compared with 21 non‐RA controls matched for age, sex, body mass index, and metabolic syndrome. Results: Compared with controls, body composition was altered in RA with a decrease in total and appendicular lean mass, whereas fat composition was not modified. Among RA patients, 28.6% had a skeletal muscle mass index below the cut‐off point for sarcopaenia (4.8% of controls). After 1 year of treatment with TCZ, there was a significant weight gain without changes for fat mass. In contrast, an increase in lean mass was observed with a significant gain in appendicular lean mass and skeletal muscle mass index between 6 and 12 months. Distribution of the fat was modified with a decrease in trunk/peripheral fat ratio and an increase in subcutaneous adipose tissue. No changes for waist circumference, blood pressure, fasting glucose, and atherogenic index were observed. Conclusions: Despite weight gain during treatment with TCZ, no increase in fat but a modification in fat distribution was observed. In contrast, muscle gain suggests that blocking IL‐6 might be efficient in treating sarcopaenia associated with RA.